Research progress of sensor-cloud security - Tian WANG; Yang LI; Weijia JIA; Guojun WANG; Shaoliang PENG (Tongxin xuebao)
Through consulting lots of domestic and international literatures about sensor-cloud security,a series of security problems are found,such as reputation problem of service provider,the coupling problem of physical nodes,the leak of authority management,et al,which seriously hinders the further development of sensor-cloud.The secure problems occurring in sensor-cloud were analyzed,the current secure technologies were contrasted ,similarities and differences of various types solutions were discussed and summarized.After that,several future challenges of sensor-cloud security were concluded.Finally,a fog-based structure was proposed to solve the security problems,which would bring new ideas to the sensor-cloud security research.